30 Testosterone (T) Recovery Profiles After Short-Term Androgen Deprivation Therapy (ADT). Issue 1 (1st April 2022) - Flores Martinez, J; Nascimento, B; Benfante, N; Schofield, E; Mulhall, JP
ABSTRACT: Introduction: ADT plays a major role in several scenarios for men with prostate cancer. T recovery after ADT cessation may be incomplete with 10% of men estimated to suffer persistent castrate levels after long-term ADT. Objective: The objective of this study was to evaluate T recovery after short courses of ADT. Methods: Study population included men treated with ≤6 months of ADT in association with radiation therapy (RT). Early morning T levels were collected at baseline and periodically after ADT cessation. T recovery after ADT cessation was analyzed in 2 ways: improvement to non-castrate level (T ≥50 ng/dL), and recovery to normal (T ≥ 300 ng/dL). Recovery rates and median survival time were estimated using Kaplan-Meier statistics and predictors analyzed using Cox proportional hazard ratios. Results: 88 men with a mean age of 68 ± 8 years at time of ADT were analyzed. Median duration of ADT was 3.1 months; 56% had an ADT duration between 1-3 months and 44% between 4-6 months. Mean pre-ADT T level was 390 ± 158 ng/dL. After cessation of ADT, median time to non- castrate levels was 9.3 (IQR = 6.3 – 18.5) months and 15.8 (IQR = 8.3 - 33.8) 'months for recovery to T ≥300 ng/dL. Higher baseline T levels (T > 400 ng/dL) was associated with a faster recovery to normal T level (HR = 1.80, 95% CI = 1.09 – 2.95), but not to non-castrate level. Neither age > 65 years, prevalent diabetes, nor ADT duration of 4-6 months vs ≤ 3 months were significantly associated with a slower T recovery. Conclusions: Most of our patients remained with low T levels one year after the cessation of ADT. Higher baseline T was associated with faster T recovery to normal (T ≥ 300 ng/dL). Disclosure: No